Efektivitas Ekstrak Buah Adas (Foeniculum vulgare) Terhadap Penurunan Kadar Glukosa Darah - Siti Maharani; Intanri Kurniati; Agustya Tjiptaningrum (CV. Jasa Sukses Abadi, 2023)
Diabetes mellitus is a condition that occurs when blood glucose levels exceed normal limits. This is caused by the pancreas not producing enough insulin or because the insulin produced is not effective in helping the absorption of glucose into the body's cells. The prevalence of diabetes in 2019 in the world is estimated to reach 463 million people aged 20-79 years. Diabetes mellitus affects more men in the world, namely 9.65% of the world's population, while the prevalence of sufferers is female as much as 9%. Indonesia is ranked 7th with the most diabetes mellitus sufferers in the world. Indonesia has as many as 10.7 million people with diabetes mellitus recorded. DKI Jakarta ranks first with the most diabetes mellitus sufferers in Indonesia, namely 3.4% of the population. Diabetes mellitus treatment does not aim to cure the disease completely, but only to control blood sugar levels so that they are within normal limits. One of the causes of diabetes mellitus is due to oxidative stress. One of the herbal plants known to have antioxidant content is fennel fruit (Foeniculum vulgare). occurrence of oxidative stress. Fennel contains flavonoids, saponins, cardiac glycosides, terpenoids, and tannins. These compounds have an antihyperglycemic effect by inhibiting alpha glucosidase. Flavonoids are antioxidant compounds that can play a role in preventing oxidative stress associated with diabetes mellitus.